Targeting host cell proteases as a potential treatment strategy to limit the spread of SARS‐CoV‐2 in the respiratory tract - Ismail A. El‐Shimy; Mahmoud M. A. Mohamed; Syed Shahzad Hasan; Muhammad A. Hadi (Wiley, 2021)
Abstract As the death toll of Coronavirus disease 19 (COVID‐19) continues to rise worldwide, it is imperative to explore novel molecular mechanisms for targeting SARS‐CoV‐2. Rather than looking for drugs that directly interact with key viral proteins inhibiting its replication, an alternative and possibly add‐on approach is to dismantle the host cell machinery that enables the virus to infect the host cell and spread from one cell to another. Excellent examples of such machinery are host cell proteases whose role in viral pathogenesis has been demonstrated in numerous coronaviruses. In this review, we propose two therapeutic modalities to tackle SARS‐CoV‐2 infections; the first is to transcriptionally modulate the expression of cellular proteases and their endogenous inhibitors and the second is to directly inhibit their enzymatic activity. We present a nonexhaustive collection of clinically investigated drugs that act by one of these mechanisms and thus represent promising candidates for preclinical in vitro testing and hopefully clinical testing in COVID‐19 patients.